2019
DOI: 10.1080/01635581.2019.1654530
|View full text |Cite
|
Sign up to set email alerts
|

Pereskia bleo Leaves Extract Induces Cell Death via Cell Cycle Arrest and Apoptosis in Cervical Cancer Cells HeLa

Abstract: Introduction: Pereskia bleo is a leafy and edible plant, locally known as "Pokok Jarum Tujuh Bilah" which has anticancer properties. This study purposed to determine the cytotoxic effects of P. bleo leaves extracts on several well-known cancer cells and elucidate its underlying mechanism in inducing cell death. Methods: Cytotoxic activity on selected cell lines was determined using MTT assay. Mechanism of cell death was investigated through cell cycle and Annexin V assay. Expression of apoptotic proteins was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Some studies reported the antiproliferative properties and mechanism of actions of P. bleo extracts against selected human cancer cell lines, i.e. nasopharyngeal epidermoid carcinoma, colon carcinoma, cervical and breast carcinoma [4,6,[12][13][14] . Breast and prostate cancers were the conditions for which P. bleo was used by our participants.…”
Section: Medical Conditionsmentioning
confidence: 99%
“…Some studies reported the antiproliferative properties and mechanism of actions of P. bleo extracts against selected human cancer cell lines, i.e. nasopharyngeal epidermoid carcinoma, colon carcinoma, cervical and breast carcinoma [4,6,[12][13][14] . Breast and prostate cancers were the conditions for which P. bleo was used by our participants.…”
Section: Medical Conditionsmentioning
confidence: 99%
“…Cancer is a group of malignant diseases characterized by uncontrolled, abnormal cells (Gurunanselage Don & Yap, 2019). It has been categorized as a disease with a high death rate in human history despite advancements in tools for diagnosis, treatment, and prevention (Mohd-Salleh et al, 2020). Although with various treatments and progress in reducing cancer incidence and development in chemotherapeutic strategies, the cases keep increasing and are still a significant public health problem worldwide (Mahmood et al, 2020).…”
Section: Introductionmentioning
confidence: 99%